2017
DOI: 10.29328/journal.jpsp.1001003
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical content of leaf and stem of Marsilea quadrifolia (L.)

Abstract: The present study was aimed to screen and quantify the phytochemicals by qualitative and quantitative analysis in methanol and aqueous leaf and stem extracts of Marsilea quadrifolia (L.). In qualitative analysis, the phytochemical compounds such as tannins, saponins, fl avonoids, steroids, terpenoids, triterpenoids, alkaloids, carbohydrates, proteins, anthroquinones, phenolic compounds and phytosterol were screened. Among these phytocompounds tannins, saponins, fl avonoids, steroids, alkaloids, carbohydrates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Since, quercetin was reported to improve the health of experimental animals’ when used even in lower doses ( Geng et al, 2019 ). Also, as indicated by Gopalakrishnan and Udayakumar (2017) and Zhang et al (2016) , the M. quadrifolia extracts may contain other quercetin derivatives and important phytoconstituents which may be responsible for significant adjuvant pharmacological actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, quercetin was reported to improve the health of experimental animals’ when used even in lower doses ( Geng et al, 2019 ). Also, as indicated by Gopalakrishnan and Udayakumar (2017) and Zhang et al (2016) , the M. quadrifolia extracts may contain other quercetin derivatives and important phytoconstituents which may be responsible for significant adjuvant pharmacological actions.…”
Section: Discussionmentioning
confidence: 99%
“…The plant M. quadrifolia is traditionally used to treat fever, cold, cough and for wound healing. It contains tannins, flavonoids, betulinic acid, fatty acids and sterols ( Gopalakrishnan and Udayakumar, 2017 ). It is also reported to contain quercetin, hentriacontane and some other important phytoconstituents which have important pharmacological properties ( Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Marsilea crenata is a semi-aquatic plant often found in rice fields and considered a weed [20]. It has been reported that M. crenata contains phytochemical components such as flavonoids, terpenoids, and saponins [21,22]. These components can potentially be used as a source (Damayanti, et al) of nutrients supporting spermatogenesis [23].…”
Section: Introduction mentioning
confidence: 99%
“…In this perspective, Marsilea quadrifolia (MQ) is a common Indian hydrophytic fern referred to in Indian traditional medicine as sedative and anticonvulsant (Bhattamisra et al, 2008; Sahu et al, 2012), while the leaf extracts can protect the epileptic rats against electro convulsions (Satyavati et al, 1987). Reports on the quantification of phytochemicals in methanolic leaf extract of MQ (MQLE) showed diverse medicinal properties (Gopalakrishnan & Udayakumar, 2017) with antiepileptic nature in maximal electroshock and PTZ-induced rat models of epilepsy (Boyce-Rustay & Holmes, 2006; Löscher, 2002). The studies on phytochemical composition and quantification of phytocompounds of MQ are limited; no report is available on the modulation of cognitive behavior by MQLE during a seizure in rats.…”
mentioning
confidence: 99%